Effects of Gagne’s Nine Events of Instruction on Biology Students Academic Performance in Tarauni, Kano State - MUSA, Gali; SHEHU, Saudat Bala; IBRAHIM, Sallau Ahmad; HARAZIMI, Ali Chigari; AHMAD, Insaff Muhammad (Ilorin Journal of Education, 2024)
The study examined the effects of Gagne’s nine events of instruction on Biology students’ academic performance in Tarauni, Kano State. The study adopted quasi-experimental control group design employing the use of pretest and posttest. The population consists of 2493 senior secondary students in Tarauni, Kano State. A sample of 200 students was randomly selected from four schools out of 21 schools that formed the population. The instrument Genetic Concept Performance Test (GCPT) was validated by experts in the field of test and measurement. The test retest reliability coefficient of the instrument was 0.85. The subjects in the experimental group were taught using Gagne’s nine events of instruction, while the subjects in the control group were taught using Lecture Method. Research questions were analyzed descriptively while null hypotheses were tested using t-test. The major finding of the results showed that there was a significant difference between the performance mean scores of students taught genetics concept using Gagne’s nine events of instructional strategy and those taught using lecture method in favor of experimental group. There was no significant difference between the mean performance scores of male and female students taught genetics concept using Gagne’s nine events of instructional strategy. Based on the findings, it was recommended that the use of Gagne’s nine events of instructional strategy should be emphasized in secondary schools across the state.